Utilization of Agricultural Waste Substrates with Inorganic Salt Medium as Nutrient Enhancer for Biosurfactant Production by MEOR-Oriented Bacterial Consortia - Nanda Ravenia Amanda; Eko Andrijanto; Bevi Lidya (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2025)
The decline in oil recovery during secondary processes has led to the exploration of tertiary methods such as Microbial Enhanced Oil Recovery (MEOR). This study investigates biosurfactant production by Pseudomonas aeruginosa and Bacillus subtilis in a co-culture system, optimizing fermentation media and evaluating effectiveness in oil recovery. Seven media were tested based on optical density (OD600), emulsification index (E24), oil displacement area (ODA), and yield of wet crude biosurfactant, observed over five days. The highest E24 value, 89.66% was recorded on day two using used lubricant as the water-immiscible phase. The best ODA values were 44.49 cm² for supernatant (ODA SNT) and 55.86 cm² for wet crude biosurfactant (ODA CBS). The optimized production medium contained 2% (v/v) waste cooking oil, 1% (w/v) molasses, and 1% (v/v) tofu wastewater. Partial purification of the culture broth through acid precipitation and solvent extraction yielded the highest wet crude biosurfactant on day three, reaching 155 g/L. The co-culture system at a 1:1 P/B ratio effectively reduced oil-water interfacial tension, as demonstrated by the high ODA values, particularly in the purified crude biosurfactant. This highlights the eco-friendly potential of biosurfactants for MEOR applications.